2020
DOI: 10.1038/s41598-020-69526-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental variation in educational attainment: an individual-based analysis of 28 twin cohorts

Abstract: We investigated the heritability of educational attainment and how it differed between birth cohorts and cultural-geographic regions. A classical twin design was applied to pooled data from 28 cohorts representing 16 countries and including 193,518 twins with information on educational attainment at 25 years of age or older. Genetic factors explained the major part of individual differences in educational attainment (heritability: a 2 = 0.43; 0.41-0.44), but also environmental variation shared by co-twins was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 38 publications
11
79
0
Order By: Relevance
“…For direct genetic effects, estimates for educational achievement were significantly larger than attainment. This finding agrees with previous twin evidence, which suggested ~60% heritability for educational achievement measured in childhood and adolescence (Rimfeld et al, 2018) and ~40% for educational attainment measured in adulthood (Branigan, McCallum, & Freese, 2013; Silventoinen et al, 2020). Some plausible explanations of such higher heritability/direct genetic effects for educational achievement are discussed in the supplement (section 7.5).…”
Section: Discussionsupporting
confidence: 93%
“…For direct genetic effects, estimates for educational achievement were significantly larger than attainment. This finding agrees with previous twin evidence, which suggested ~60% heritability for educational achievement measured in childhood and adolescence (Rimfeld et al, 2018) and ~40% for educational attainment measured in adulthood (Branigan, McCallum, & Freese, 2013; Silventoinen et al, 2020). Some plausible explanations of such higher heritability/direct genetic effects for educational achievement are discussed in the supplement (section 7.5).…”
Section: Discussionsupporting
confidence: 93%
“…Overestimating heritability would lead to overestimating genetic confounding and thus underestimating the residual association between exposure and outcome. For example, a recent study of 193,518 twins across 16 countries has showed that educational attainment is 43% heritable [24]. As can be seen in Figure 1, this lower estimate would lead to a substantially larger adjusted association.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that observed shrinkage is likely to be largely driven by assortative mating or indirect genetic effects since both of these tend to influence associations proportional to the direct effect (whereas population stratification is likely to have larger effects on ancestrally informative markers). The common environment terms from classical twin studies suggest that there are likely to be indirect genetic effects on educational attainment [41], cognitive ability [42] and smoking [43], but suggest that the observed shrinkage for height is likely to be a consequence of assortative mating [10, 43, 44].…”
Section: Discussionmentioning
confidence: 99%